2019
DOI: 10.3390/coatings9030196
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Stoichiometry of NbxNy Coatings Produced by DC Magnetron Sputtering with Electrical Conductivity and the Hall Coefficient

Abstract: Non-stoichiometric NbxNy coatings, produced in a reactive sputtering process, were analyzed on the basis of their chemical composition (specifically, nitrogen concentration) and its relationship with electrical conductivity. The chemical composition and bonding configuration were examined using X-ray photoelectron spectroscopy (XPS), revealing Nb–N bonds. The stoichiometry variation dependence on the N2 flow was also analyzed, using Auger electron spectroscopy (AES). Without exposing the samples to air, a norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…It also needs to be noted that stainless steels are not intrinsically good electrical conductors. It has been reported that the conductivity of NbN is around 3 × 10 Ω −1 cm −1 (at 25 • C), which is much higher than that for Cr 2 O 3 (<10 −3 Ω −1 cm −1 ) [43,44]. Among all the coated specimens, the Nb coating exhibited the lowest ICR (9 mΩ•cm 2 ), which satisfied the U.S. DOE requirement (≤10 mΩ•cm 2 ) [45].…”
Section: Interfacial Contact Resistance Measurementmentioning
confidence: 93%
“…It also needs to be noted that stainless steels are not intrinsically good electrical conductors. It has been reported that the conductivity of NbN is around 3 × 10 Ω −1 cm −1 (at 25 • C), which is much higher than that for Cr 2 O 3 (<10 −3 Ω −1 cm −1 ) [43,44]. Among all the coated specimens, the Nb coating exhibited the lowest ICR (9 mΩ•cm 2 ), which satisfied the U.S. DOE requirement (≤10 mΩ•cm 2 ) [45].…”
Section: Interfacial Contact Resistance Measurementmentioning
confidence: 93%